2020
DOI: 10.1002/jgh3.12444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced magnetic resonance imaging on the prognosis of hepatocellular carcinoma after surgery

Abstract: Background and Aim: Gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (EOB-MRI) has been recognized as a useful imaging technique to distinguish the biological behavior of hepatocellular carcinoma (HCC). Methods: We analyzed 217 hepatectomy recipients with HCCs measuring 10 cm or less. We divided the patients into a decreased intensity (DI) group (n = 189, 87%) and an increased or neutral intensity (INI) group (n = 28, 13%) according to the ratio of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The compound is secreted into bile 10-20 min after injection. Several studies have demonstrated that MRI using Gd-EOB-DTPA provides diagnostic accuracy for liver lesions and HCC [50,51]. However, it is essential to take into account that genetic polymorphisms affecting liver transporters for organic anions [organic anion transporting polypeptides (OATPs)] (Figure 2), as well as some drug interactions, can decrease Gd-EOB-DTPA uptake by hepatocytes.…”
Section: Probes Based On Gadoliniummentioning
confidence: 99%
“…The compound is secreted into bile 10-20 min after injection. Several studies have demonstrated that MRI using Gd-EOB-DTPA provides diagnostic accuracy for liver lesions and HCC [50,51]. However, it is essential to take into account that genetic polymorphisms affecting liver transporters for organic anions [organic anion transporting polypeptides (OATPs)] (Figure 2), as well as some drug interactions, can decrease Gd-EOB-DTPA uptake by hepatocytes.…”
Section: Probes Based On Gadoliniummentioning
confidence: 99%
“…Some clinical factors, such as the Barcelona Clinic Liver Cancer (BCLC) stage, microvascular invasion (MVI), serum alpha-fetoprotein (AFP), number or size of the tumor(s), hypointensity in the hepatobiliary phase, and incomplete capsule, are associated with postoperative prognosis [ [6] , [7] , [8] , [9] ]. Additionally, various nomograms based on staging systems have been developed to predict HCC outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%